Sistema para la automatización y tele-gestión de la banda transportadora del Laboratorio de Automatización Industrial (2019)
As of 2019, the Departamento de Ingeniería Eléctrica y Electrónica is in charge of the recovery of the old Robotics Laboratory, which has been renamed "Laboratorio de Automatización Industrial". This Laboratory has equipment capable of emulating an industrial production process, but which is currently out of service due to the obsolescence of its computing brains. It is a closed and proprietary system that involves high costs and low interaction from the educational point of view.  The tConBelt system is a platform that allows to emulate a solution for industrial automation oriented to Industry 4.0. The system designed and built, offers the user remotely speed control, speed sensing, and management of energy consumption parameters of the conveyor belt of the Industrial Automation laboratory, from any terminal connected to the Internet, either from an interface web or a native application on Android. The data repository in the Cloud allows real-time data tracking, and a historical query.